IDENTIFIKASI TERUMBU KARANG PERAIRAN MAMBURIT KEBUPATEN SUMENEP - Sawiya Sawiya (Faculty of Science and Technology University Ibrahimy, 2015)
Research conducted in September through October 2013 in waters Mamburit Sumenep. This study aims to determine the percentage and types of coral. The material used consists of coral reefs, using the LIT (Line Intercept) stretched parallel to the coastline at a depth of 3 meters and 10 meters in the area Winward and leeward identification for coral reefs. The percentage of live coral reefs in the area Leeward depth of 3 meters of living coral reef percentage 59.88% good category and the percentage of dead coral reefs and other fauna as much as 40.12% a depth of 10 meters the percentage of living coral reefs as much as 69.19% medium category and the percentage of dead coral reefs and other fauna 30.81%. Location Winward depth of 3 meters percentage of living coral reefs as much as 68.38%, including both categories and the percentage of dead coral reefs and other fauna as much as 31.62% and to a depth of 10 meters the percentage of live coral reefs 40.86% is average and the percentage of dead coral reefs and other fauna 59.14%.